Spreadsheet Use and Programming Experience: an Exploratory Survey - Sarkar, Advait; Borghouts, Judith W.; Iyer, Anusha; Khullar, Sneha; Canton, Christian; Hermans, Felienne; Gordon, Andy; Williams, Jack (38th Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems (CHI '20 Extended Abstracts), 2020)
We report results from a survey on spreadsheet use and experience with textual programming languages (n= 49). We find significant correlations between self-reported formula experience, programming experience, and overall spreadsheet experience. We discuss the implications of our findings for spreadsheet research and end-user programming research, more generally.